African Development and Public Policy
XIII, 287 p.
Keywords: This book analyzes various important aspects of methodology and substance regarding economic, social, and political policy in Africa directed toward achieving more effective, efficient, and equitable societal institutions. The chapters are authored by experts from within Africa and also from Africa research institutes elsewhere. The book combines practical policy significance with insightful causal and prescriptive generalizations. The emphasis is on the role of governmental decision-making and the important (but secondary) role of the marketplace, social groups, and engineering.